New directions for healthy working environments (HWE) policy: A qualitative systematic review of attempts to reframe occupational safety and health (OSH) - Eli Auslender; Lukas Fuchs; Paul Cairney (Open Research Europe, 2026)
Background ‘Healthy working environment’ (HWE) describes an ambitious research and policy agenda for occupational safety and health (OSH). It signals a shift from a narrow focus on the avoidance of immediate workplace physical harms towards a wider concern with the longer-term occupational, social, and environmental contributors to physical and mental health and wellbeing. We examine how researchers and policymakers define this aim and what policy instruments they recommend. We then focus on the European Union to examine who may be responsible for making, implementing, or influencing the design of each instrument. Methods A qualitative systematic review (2025–26) to identify academic journal articles (Web of Science) and grey literature reports (Policy Commons) on HWE and OSH policy and policymaking, then snowballing to identify key academic and policy reference points. We draw insights from policy theories to inform an inductive approach that identifies key policy problem, policy mix, and policy process themes in the HWE literature. Results HWE represents ambiguous aspirations for policy change. This ambiguity exacerbates uncertainty about which policy instruments should be used, and who should adopt them. EU research highlights hard regulations to enforce minimum OSH standards but soft guidance to encourage HWE innovation, contributing to the sharing of responsibilities between state and non-state organisations. Organisational research highlights greater scope for HWE change among large companies in sectors that reward innovation. Conclusion HWE signals an ambitious but ambiguous definition of OSH. In the EU, it symbolises the rhetorical pursuit of higher ambitions but lower substantive state intervention. There is some evidence of organisational innovation, but not on a scale consistent with EU ambitions.